Effects of Circadian Phase Tailored Light Therapy on Sleep, Mood, and Cognition in Alzheimer’s Disease: Preliminary Findings in a Pivotal Study - Cremascoli, Riccardo; Sparasci, Davide; Giusti, Gianluca; Cattaldo, Stefania; Prina, Elisa; Roveta, Fausto; Bruno, Francesco; Ghezzi, Cristina; Cerri, Silvia; Picascia, Marta; Bernini, Sara; Sinforiani, Elena; et al. (Frontiers in Physiology, 2022)
It is shown that the circadian system is affected in patients with Alzheimer’s disease (AD) even at an early stage of the disease and that such dysfunction may be detrimental to sleep, mood and cognitive functioning. Light is a strong central modulator of the circadian rhythms and is potentially beneficial to mood and cognitive functioning via a direct effect or indirectly via its modulating effects on circadian rhythms. This article focuses on tracking the effect of light therapy on sleep quality, mood and cognition in AD of mild/moderate severity. We performed a single-blind randomised control trial to investigate the effects of a light therapy treatment tailored to the individual circadian phase as measured by DLMO. Such a treatment induced an objective circadian phase shift consistent with the melatonin phase response curve to light exposure, led to a shortening of the phase angle DLMO-Falling asleep time, and was associated with an improvement in subjective sleep quality and cognitive performance.